ATP synthesis driven by atmospheric hydrogen concentrations - Sarah Soom; Stefan Urs Moning; Gregory M. Cook; James P. Lingford; Ashleigh Kropp; Sieu Tran; Rhys Grinter; Chris Greening; Christoph von Ballmoos (Proceedings of the National Academy of Sciences, 2025)
All cells require a continuous supply of the universal energy currency, adenosine triphosphate (ATP), to drive countless cellular reactions. The universally conserved F 1 F o -ATP synthase regenerates ATP from ADP and P i by harnessing a transmembrane electrochemical proton gradient ( pmf ). Bacteria have evolved diverse pmf -forming strategies using light, organic, and inorganic energy sources. Recently, we proposed that many bacteria survive using atmospheric trace gases to produce ATP when limited for other energy sources. However, direct evidence that atmospheric energy sources are sufficient to generate pmf or drive ATP synthesis is still lacking. Here, we show that the membrane-associated hydrogen:quinone oxidoreductase Huc from Mycobacterium smegmatis can enable ATP synthesis from air. Purified Huc couples H 2 oxidation to the reduction of various ubiquinone and menaquinone analogues. We designed a minimal respiratory chain in which Huc interacts with liposomes containing the nonpumping, but pmf -generating, bd -I oxidase and F 1 F o -ATP synthase from Escherichia coli . Our experiments show that passive hydrogen exchange from air to solution is sufficient for the electron transfer and pmf generation required to accumulate ATP. By combining continuous culture bioenergetics measurements with theoretical calculations, we show this process is sufficient for mycobacteria to sustain pmf and ATP synthesis (two ATP molecules per H 2 oxidized) for maintenance energy requirements during nutrient starvation. These findings confirm that atmospheric energy sources can be dependable ‘lifeline’ substrates that enable continuous energy conservation during nutrient starvation. In addition, this work provides a unique tool for ATP production in synthetic applications, which unlike other approaches is traceless without by-product accumulation.